ANALYSIS OF SETAGAYA WARD’S SYSTEM OF DEVELOPING VACANT HOUSES INTO BASES THAT ARE USEFUL TO THE COMMUNITY - Yamada, Shota (PEOPLE: International Journal of Social Sciences, 2024)
Setagaya Ward established a consultation service in July 2013 to develop vacant houses into useful bases for the community. This service matches owners of vacant houses with non-profit organizations and produced 22 bases in 10 years. Through analysis of the bases, it became clear that the majority of the bases were using vacant rooms rather than the entire house. Many bases that contribute to social welfare, such as child and disability welfare, have been created. This service can deal with cases that are difficult for private real estate companies to handle. It shows the significance for local governments to operate vacant house utilization systems.